(Acetylacetonato-κ2O,O′)(phthalocyaninato-κ4N)(phenanthroline-κ2N,N′)erbium(III) - Hong-Feng Li; Peng-Fei Yan (Acta Crystallographica Section E, 2012)
The title complex, [Er(C32H16N8)(C5H7O2)(C12H8N2)], possesses a mirror plane and the asymmetric unit is half of the molecule. The ErIII cation, lying on the mirror plane, is eight-coordinated by two O atoms from acetylacetone, two N (Nphen) atoms from 1,10-phenanthroline and four isoindole N (Niso) atoms from the phthalocyanine ligand in an antiprismatic geometry. The Er—N distances are in the range 2.376 (5)–2.529 (4) Å and the Er—O distance is 2.272 (3) Å. Notably, the Er—Niso bonds are shorter than the Er—Nphen bonds, but longer than the Er—O bonds.